Rheological and Viscoelastic Property Characterizations of Amino Acid-Based Hydraulic Fracturing Fluids - Quainoo, A.K. (American Chemical Society, 2022)
In this paper, we present the results of the rheometric properties of a guar-based fracturing fluid containing amino-Acid clay stabilizers. Four amino acids, glycine, proline, alanine, and arginine were selected for the study. KCl, a conventional clay stabilizer, was also used for comparison. The fracturing fluid was prepared using tap water (97.3 wt ), guar gum (0.4 wt ), ethylene glycol (0.1 wt ), potassium carbonate (0.2 wt ), and a clay stabilizer (2 wt ). A Discovery Hybrid rheometer with a bob-in-cup measuring system was used to determine the fluids' viscoelastic and temperature-dependent properties under both static and dynamic oscillatory conditions. The static tests were employed at varying shear rates of 0.001-1000 s-1from 25 to 90 Â°C, mimicking both room and reservoir conditions. For the oscillatory measurements, amplitude and frequency sweep tests were done at a strain ranging from 0.001 to 100 and a frequency ranging from 0.01 to 100 rad/s. The rheological characterizations of the fracturing fluids confirmed that amino acids did not negatively affect the base fluid's viscoelasticity, flow behavior, shear-Thinning properties, and pumpability, including its damping factor. Glycine and alanine enhanced the shear-Thinning property of the base fluid by 4 and 5, respectively. All the stabilized fluids displayed significant upsurges in their elasticity as the frequency was increased from 0.01 to 100 rad/s. Proline, glycine, and alanine improved the base fluid elasticity by reducing its damping factor value by 0.37, 0.20, and 0.14, respectively. Alanine on the other hand increased the base fluid's damping factor value by 0.12. This study provides new insights into the rheological abilities of hydraulic fracturing fluids containing amino acid additives and how their presence in the fracturing fluid contributes to the effective transportation and dropping of proppants. These insights are necessary for evaluating the effects of additives on the fracturing fluid gel structure, proppant carrying and packing capacity, gelling time, temperature stability, and, more importantly, its structural stability. Â© 2022 American Chemical Society. All rights reserved.